DAMPAK PEMBELAJARAN DARING TERHADAP DISIPLIN GURU KELAS PADA SEKOLAH DASAR - Jumadil Akhir Lubis; Nirwana Anas; Isti Ningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
This article aims to find out whether online learning has an impact on teacher discipline. At this time, we were shocked by the Covid 19 virus which required children to do online learning, this had an impact on teacher discipline. The aim of the researchers is to find out the impact of online learning on teacher discipline. The method used in this research is a qualitative approach through interviews with 10 parents of students. Informants were asked through interviews regarding the impact of online learning on teacher discipline. The results of the analysis show that in general teacher discipline is very low because it was found that teachers did not open classes online or offline, teachers did not sign attendance lists, teachers were not present at school on time, teachers did not leave class on time, teachers were also found to leave school without permission from the principal. Learning does not materialize at this school because students do not yet have facilities for online learning, the existing internet is inadequate.